Excited‐State Reactivity of [Mn(im)(CO)3(phen)]+: A Structural Exploration. Issue 1 (12th September 2018) - Fumanal, Maria; Harabuchi, Yu; Gindensperger, Etienne; Maeda, Satoshi; Daniel, Chantal
Abstract : The electronic excited state reactivity of [Mn(im)(CO)3 (phen)] + (phen = 1, 10‐phenanthroline; im = imidazole) ranging between 420 and 330 nm have been analyzed by means of relativistic spin–orbit time‐dependent density functional theory and wavefunction approaches (state‐average‐complete‐active‐space self‐consistent‐field/multistate CAS second‐order perturbation theory). Minimum energy conical intersection (MECI) structures and connecting pathways were explored using the artificial force induced reaction (AFIR) method. MECIs between the first and second singlet excited states ( S 1 / S 2 ‐MECIs) were searched by the single‐component AFIR (SC‐AFIR) algorithm combined with the gradient projection type optimizer. The structural, electronic, and excited states properties of [Mn(im)(CO)3 (phen)] + are compared to those of the Re(I) analogue [Re(im)(CO)3 (phen)] + . The high density of excited states and the presence of low‐lying metal‐centered states that characterize the Mn complex add complexity to the photophysics and open various dissociative channels for both the CO and imidazole ligands. © 2018 Wiley Periodicals, Inc. Abstract : The structural exploration of the potential energy surfaces associated with the low‐lying singlet excited states of a manganese carbonyl imidazole‐substituted α‐diimine complex, potentially functional PhotoCORM under visible irradiation, highlights the active reactive channels of dissociation. Qualitative state correlation diagrams that connect the low‐lying excited states of the parent molecule to those of the fragments [Mn(imidazole)(CO)2 (phen)] + + COax and [M(CO)3 (phen)] + + Imidazole point to two dissociative channels. The two lowest S 1 and S 2 singlet states are weakly dissociative for the CO loss with energy barriers generated nearby the FC region. Systematic searches for critical geometries identify several dissociative pathways, namely, equatorial CO bent, imidazole dissociation, or axial CO bent are competitive with the direct CO loss.